2019
DOI: 10.3892/ol.2019.10403
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑432 is downregulated in cervical cancer and directly targets FN1 to inhibit cell proliferation and invasion

Abstract: Numerous studies have identified the dysregulation of microRNAs (miRNAs) in cervical cancer, and dysregulated miRNAs are involved in regulating a number of tumourassociated biological behaviours. Therefore, investigating the roles of cervical cancer-associated miRNAs and the underlying molecular mechanisms is essential for the development of novel diagnostic biomarkers and effective therapeutic targets. MicroRNA-432 (miR-432) dysregulation has been revealed to be implicated in the carcinogenesis and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
3
21
1
Order By: Relevance
“…Overexpression of miR-106b-5p in glioma cells can promote significant cell proliferation and mediate apoptosis of glioma cells by targeting CASP8 [79]. However, in contrast to our findings, Nan et al reported that miR-432 inactivated the Wnt/β-catenin pathway by simultaneously inhibiting the expression of LRP6, TRIM29, and Pygo2, thereby inhibiting the proliferation of human hepatocellular carcinoma [80]. This may be because miRNA-432 plays a different role in different tissue cells and has tissue specificity.…”
Section: Discussioncontrasting
confidence: 99%
“…Overexpression of miR-106b-5p in glioma cells can promote significant cell proliferation and mediate apoptosis of glioma cells by targeting CASP8 [79]. However, in contrast to our findings, Nan et al reported that miR-432 inactivated the Wnt/β-catenin pathway by simultaneously inhibiting the expression of LRP6, TRIM29, and Pygo2, thereby inhibiting the proliferation of human hepatocellular carcinoma [80]. This may be because miRNA-432 plays a different role in different tissue cells and has tissue specificity.…”
Section: Discussioncontrasting
confidence: 99%
“…FN1 has been shown to promote metastasis in various types of tumors. [ 39 41 ] Recently, Li et al [ 42 ] reported that FN1 promotes cutaneous melanoma proliferation and metastasis by inhibiting apoptosis and regulating epithelial-to-mesenchymal transition, which is consistent with our results. APOA1 is the main protein constituent of high-density lipoprotein, which shuttles excess cholesterol from organs to the liver for excretion.…”
Section: Discussionsupporting
confidence: 92%
“…These results revealed that FN1 plays an important role in maintaining the dynamic balance of proliferation and apoptosis of trophoblasts during pregnancy. However, it is worth noting that FN1 has been reported to be upregulated in cervical cancer tissues and to promote cell proliferation ( 35 ). Therefore, the results of the present study only suggest that the overexpression of FN1 may be helpful for inhibiting the SA-induced apoptosis of trophoblasts, but do not indicate that the overexpression of FN1 would be helpful in other diseases.…”
Section: Discussionmentioning
confidence: 99%